Foreign Languages Sound Fast: Evidence from Implicit Rate Normalization - Bosker, Hans Rutger; Reinisch, Eva (Frontiers in Psychology, 2017)
Anecdotal evidence suggests that unfamiliar languages sound faster than one’s native language. Empirical evidence for this impression has, so far, come from explicit rate judgments. The aim of the present study was to test whether such perceived rate differences between native and foreign languages have effects on implicit speech processing. Our measure of implicit rate perception was “normalization for speaking rate”: an ambiguous vowel between short /a/ and long /a:/ is interpreted as /a:/ following a fast but as /a/ following a slow carrier sentence. That is, listeners did not judge speech rate itself; instead, they categorized ambiguous vowels whose perception was implicitly affected by the rate of the context. We asked whether a bias towards long /a:/ might be observed when the context is not actually faster but simply spoken in a foreign language. A fully symmetrical experimental design was used: Dutch and German participants listened to rate matched (fast and slow) sentences in both languages spoken by the same bilingual speaker. Sentences were followed by nonwords that contained vowels from an /a-a:/ duration continuum. Results from Experiments 1 and 2 showed a consistent effect of rate normalization for both listener groups. Moreover, for German listeners, across the two experiments, foreign sentences triggered more /a:/ responses than (rate matched) native sentences, suggesting that foreign sentences were indeed perceived as faster. Moreover, this Foreign Language effect was modulated by participants’ ability to understand the foreign language: those participants that scored higher on a foreign language translation task showed less of a Foreign Language effect. However, opposite effects were found for the Dutch listeners. For them, their native rather than the foreign language induced more /a:/ responses. Nevertheless, this reversed effect could be reduced when additional spectral properties of the context were controlled for. Experiment 3, using explicit rate judgments, replicated the effect for German but not Dutch listeners. We therefore conclude that the subjective impression that foreign languages sound fast may have an effect on implicit speech processing, with implications for how language learners perceive spoken segments in a foreign language.